The effect of oleuropein from olive leaf (Olea europaea) extract on Ca2+ homeostasis, cytotoxicity, cell cycle distribution and ROS signaling in HepG2 human hepatoma cells. (May 2016) - Cheng, Jin-Shiung; Chou, Chiang-Ting; Liu, Yuan-Yuarn; Sun, Wei-Chih; Shieh, Pochuen; Kuo, Daih-Huang; Kuo, Chun-Chi; Jan, Chung-Ren; Liang, Wei-Zhe
Abstract: Oleuropein, a phenolic compound found in the olive leaf ( Olea europaea ), has been shown to have biological activities in different models. However, the effects of oleuropein on Ca 2+ homeostasis, cytotoxicity, cell cycle distribution and ROS signaling in liver cells have not been analyzed. Oleuropein induced [Ca 2+ ]i rises only in HepG2 cells but not in AML12, HA22T or HA59T cells due to the different status of 3-hydroxy-3-methylglutaryl-CoA reductase expression. In HepG2 cells, this Ca 2+ signaling response was reduced by removing extracellular Ca 2+, and was inhibited by the store-operated Ca 2+ channel blockers 2-APB and SKF96365. In Ca 2+ -free medium, pretreatment with the ER Ca 2+ pump inhibitor thapsigargin abolished oleuropein-induced [Ca 2+ ]i rises. Oleuropein induced cell cycle arrest which was associated with the regulation of p53, p21, CDK1 and cyclin B1 levels. Furthermore, oleuropein elevated intracellular ROS levels but reduced GSH levels. Treatment with the intracellular Ca 2+ chelator BAPTA-AM or the antioxidant NAC partially reversed oleuropein-induced cytotoxicity. Together, in HepG2 cells, oleuropein induced [Ca 2+ ]i rises by releasing Ca 2+ from the ER and causing Ca 2+ influx through store-operated Ca 2+ channels. Moreover, oleuropein induced Ca 2+ -associated cytotoxicity that involved ROS signaling and cell cycle arrest. This compound may offer a potential therapy for treatment of human hepatoma. Graphical abstract: Highlights: The investigation of oleuropein-induced [Ca 2+ ]i rises and cytotoxicity was explored in liver cells. Oleuropein induced [Ca 2+ ]i rises by releasing Ca 2+ and causing Ca 2+ influx in HepG2 cells. Oleuropein induced Ca 2+ -associated apoptosis in HepG2 cells. Oleuropein evoked ROS signaling and cell cycle arrest in HepG2 cells.